Professional quality of life in home visitors: Core components of the reflective supervisory relationship and IMH‐E® Endorsement® engagement. Issue 2 (10th February 2022) - Eaves, Tanika; Robinson, JoAnn L.; Brown, Edna; Britner, Preston
Abstract: Infant and early childhood home visiting models are gaining prominence as effective programs for families. Most U.S. state infant mental health associations (IMHAs) recommend reflective supervision (RS) and Infant Mental Health (IMH‐E ® ) Endorsement ® as components of home visitor professional development. These efforts may promote workforce professional quality of life. It is unknown whether a workplace policy to provide RS improves the likelihood that best practice guidelines, especially core components of a reflective supervisory relationship, are experienced by the workforce. We sought to investigate associations between home visitor well‐being indicated by professional quality of life (i.e., burnout, secondary traumatic stress, compassion satisfaction) and a workplace policy providing RS, consistent experience of core components of a reflective supervisory relationship, and engagement in endorsement. We also examined differences in consistently experiencing core components of the reflective supervisory relationship in home visitors who reported having a workplace policy for providing RS and those who did not, and for home visitors engaged or not engaged in the endorsement process. A Workplace Supports Survey was designed to investigate these associations; we report findings from a sample of home visitor respondents ( N = 139). A policy to provide RS was not associated with professional quality of life. However, analyses suggest an association between a policy to provide RS and consistently experiencing core components of a reflective supervisory relationship. Unanticipated positive associations between engagement in endorsement and burnout and secondary traumatic stress were also found. Finally, engagement in endorsement was associated with less consistent experience of these core components. Implications for future inquiry about the purposes of RS and IECMH Endorsement ® as strategies to promote workforce development and well‐being are discussed. Resumen: Los modelos de visitas a casa en el campo de la infancia y la temprana niñez han adquirido importancia como programas eficaces para familias. La mayoría de las asociaciones estatales de salud mental infantil en Estados Unidos promueven la supervisión con reflexión (RS) y en Endoso® de Salud Mental Infantil (IMH‐E®) como recursos de desarrollo profesional. RS y el Endoso® IMH‐E® pudieran también promover la calidad de vida de la fuerza laboral profesional. Se desconoce si una política laboral de proveer RS se asocia con la experiencia de la fuerza laboral y las mejores directrices en la práctica, incluyendo los componentes centrales de una relación de supervisión con reflexión (CCRSR). Investigamos las asociaciones entre la calidad de vida profesional del visitante a casa (v.g. cansancio, estrés traumático secundario, satisfacción en la compasión) y una política laboral para RS, la experiencia consistente de CCRSR y la participación en el endoso. Una Encuesta sobre los Apoyos Laborales se diseñó para investigar estas asociaciones; nosotros reportamos los resultados de un grupo muestra de visitadores a casa (N = 139). Una política para ofrecer RS no se asoció con la calidad de vida profesional. Sin embargo, los análisis indican una asociación entre una política para ofrecer RS y experimentar consistentemente CCRSR. Se observaron asociaciones positivas no anticipadas entre la participación en el endoso y el cansancio y estrés traumático secundario. Finalmente, la participación en el endoso se asoció con una menos consistente experiencia de CCRSR. Se discuten las implicaciones para consulta futura acerca de los propósitos de RS y el Endoso® IECHM como estrategias para promover el desarrollo y bienestar de la fuerza laboral. Résumé: Les modèles de visite à domicile du nourrisson/de la petite enfance ont gagné en importance en tant que programmes efficaces pour les familles. La plupart des associations de santé mentale du nourrisson au niveau des états aux USA font la promotion de la supervision réflective (RS) et de l'adoption Infant Mental Health (IMH‐Eâ) en tant que ressources de développement professionnel. La RS et l'adoption IMH‐Eâ peuvent aussi promouvoir la qualité de vie professionnelle des effectifs. On ne sait pas si le fait d'offrir la RS au travail est lié à l'expérience des effectifs des lignes directrices des pratiques exemplaires y compris les composants essentiels d'une relation de supervision réflective (CCRSR). Nous avons étudié les liens entre la qualité de vie professionnelle d'un visiteur à domicile (i.e. burnout, stress traumatique secondaire, satisfaction de compassion) et le fait d'avoir la RS au travail, l'expérience constante de la CCRSR et l'engagement dans l'adoption. Un Questionnaire de Soutien du Lieu de Travail a été conçu pour étudier ces liens. Nous faisons état des résultats à partir d'un échantillon de visiteurs à domicile (N = 139). Le fait d'offrir la RS n'était pas lié à la qualité de vie professionnelle. Cependant les analyses suggèrent un lien entre le fait d'offrir la RS et le fait de faire l'expérience de la CCRSR avec constance. Des liens positifs inattendus entre l'engagement d'adoption et le burnout et le stress traumatique secondaires ont été observés. Enfin, l'engagement d'adoption était lié à une expérience moins constante de la CCRSR. Les implications pour des recherches futures sur les objectifs de la RS et de l'adoption IECMH en tant que stratégies de promotion du développement et du bien‐être au travail sont discutées. Zusammenfassung: Berufliche Lebensqualität bei Hausbesuchenden: Kernkomponenten der reflexiven supervisorischen Beziehung und des „Infant Mental Health Endorsement" (IMH‐E) Hausbesuchsmodelle für Säuglinge und Kleinkinder haben sich als effektive Programme für Familien etabliert. Die meisten US‐amerikanischen Verbände für die psychische Gesundheit von Kleinkindern fördern reflexive Supervision (RS) und das „Infant Mental Health Endorsement" (IMH‐E) als professionelle Entwicklungsressourcen. RS und IMH‐E könnten sich auch positiv auf die berufliche Lebensqualität von Fachkräften auswirken. Es ist nicht bekannt, ob Arbeitsplatzrichtlinien für die Bereitstellung von RS damit assoziiert sind, wie Mitarbeitende Best‐Practice‐Leitlinien einschließlich der Kernkomponenten einer reflexiven Supervisionsbeziehung (core components of a reflective supervisory relationship; CCRSR) erleben. Wir untersuchten den Zusammenhang zwischen beruflicher Lebensqualität von Hausbesuchenden (d. h. Burnout, sekundärer traumatischer Stress, Zufriedenheit mit Empathievermögen) und Arbeitsplatzrichtlinien für RS, dem konsistenten Erleben von CCRSR und dem Einsatz für „Endorsement". Um diese Zusammenhänge zu untersuchen, wurde eine Umfrage zur Unterstützung am Arbeitsplatz konzipiert. Berichtet wird über die Ergebnisse einer Stichprobe von Hausbesuchenden (N = 139). Richtlinien zur Bereitstellung von RS waren nicht mit der beruflichen Lebensqualität assoziiert. Die Analysen deuten jedoch auf einen Zusammenhang zwischen Richtlinien zur Bereitstellung von RS und dem konsistenten Erleben von CCRSR hin. Es ergaben sich unerwartete positive Assoziationen zwischen dem Einsatz für „Endorsement" und Burnout sowie sekundärem traumatischem Stress. Schließlich war der Einsatz für „Endorsement" mit einem weniger konsistenten Erleben von CCRSR assoziiert. Implikationen für zukünftige Untersuchungen zur Aufgabe von RS und IECMH‐Endorsement als Strategien zur Förderung der Personalentwicklung und des Wohlbefindens werden diskutiert. 抄録: 家庭訪問実行者の専門家としての生活の質:内省的スーパービジョンにおける関係性の中核的要素と乳幼児精神保健 (IMH‐E®) 認定への取り組み 乳幼児期の家庭訪問モデルは、家族にとって効果的なプログラムとして注目されている。米国のほとんどの州の乳幼児精神保健協会は、専門家養成資源として、内省的スーパービジョン (RS) と乳幼児精神保健 (IMH‐E®) 認定を推進している。RSとIMH‐E®は、従事者の専門家としての生活の質を高める可能性もある。RSを提供するという職場の方針と、内省的スーパービジョンにおける関係性の中核的要素 (CCRSR) を含む最善の臨床ガイドラインを従事者が経験することとの関連は不明である。本研究では、家庭訪問者の専門家としての生活の質 (例 燃え尽き、二次的外傷性ストレス、情緒的満足度) と、職場でのRS提供方針、CCRSRの安定した経験、認定に取り組んでいるかとの関連を調査した。これらの関連性を調査するために「職場支援調査」を作成した。家庭訪問者集団 (N = 139) から得られた結果を報告する。RSを提供するという方針は、専門家としての生活の質とは関連しなかった。しかし、解析の結果、RSを提供する方針とCCRSRを安定して経験していることとの間には関連があることが示唆された。認定への取り組みと燃え尽きおよび二次的外傷性ストレスとの間には、予想外の正の関連が認められた。最後に、認定への取り組みは、CCRSRを経験する安定性の低さと関連していた。専門家の成長と幸福を促進する戦略としてのRSとIECMH認定の目的について、今後の調査への影響が論じられる。 摘要: 幼儿时期家访模式作为一种有效的家庭计划, 已越来越受到重视。大多数美国州立婴儿心理健康协会将反思性监督 (RS) 和婴儿心理健康认证 (IMH‐E®) 作为专业发展资源。RS和IMH‐E®还可以提高员工的职业生活质量。目前尚不清楚提供RS的工作场所政策是否与最佳实践指南 (包括反思性监督关系的核心组成部分, CCRSR) 的员工体验相关。我们调查了家庭访问者的职业生活质量 (即倦怠、继发性创伤压力、同情心满意度) 与RS的工作场所政策、CCRSR的持续体验以及参与认证之间的关联。"工作场所支持度调查"被用于研究这些关联;我们报告了来自家庭访问者样本 (N = 139) 的调查结果。提供RS的政策与职业生活质量无关。然而, 分析表明, 提供RS的政策与持续体验CCRSR之间存在关联。我们观察到, 参与认证与倦怠、继发性创伤压力之间存在意料之外的正相关。最后, 参与认证与较少的CCRSR持续体验相关。论文还讨论了, 将RS和IECMH认证作为提升员工发展和幸福感战略的目的, 对未来调查的意义。 ملخص: جودة الحياة المهنية عند زوار المنزل : المكونات الأساسية للعلاقة الإشرافية التأملية ودعم مشاركة الصحة النفسية للرضع (IMH‐E) المشاركة اكتسبت نماذج الزيارات المنزلية للرضع والطفولة المبكرة مكانة بارزة كبرامج فعالة للعائلات. تعزز معظم هيئات واتحادات الصحة النفسية للرضع في الولايات المتحدة الإشراف التأملي (RS) ودعم مشاركة الصحة النفسية للرضع (IMH‐Eâ) كمصادر للتطوير المهني. وهذه المصادر قد تعزز أيضًا جودة الحياة المهنية للعاملين. من غير المعروف ما إذا كانت سياسة مكان العمل لتوفير الإشراف التأملي مرتبطة بتجربة العاملين لإرشادات أفضل الممارسات بما في ذلك المكونات الأساسية للعلاقة الإشرافية التأملية . تناولنا في هذه الدراسة الارتباطات بين جودة الحياة المهنية للزائر المنزلي (أي الإرهاق والإجهاد الثانوي الناتج عن الصدمة والرضا والتعاطف) وسياسة مكان العمل نحو الإشراف التأملي والتجربة المتسقة لمكونات علاقة الإشراف التأملي والمشاركة في الدعم. تم تصميم استطلاع دعم مكان العمل للتحقيق في هذه الارتباطات ؛ وتقدم الدراسة النتائج من عينة من زوار المنزل (العدد = 139). لم يكن هناك ارتباط بين سياسة توفير خدمات شخصية و جودة الحياة المهنية. ومع ذلك ، تشير التحليلات إلى وجود ارتباط بين سياسة لتوفير الإشراف التأملي وتجربة مكونات العلاقة الإشرافية باستمرار. ولوحظ وجود ارتباطات إيجابية غير متوقعة بين المشاركة في التأييد والإرهاق والإجهاد الصادم الثانوي. أخيرًا ، ارتبط الاشتراك في الدعم بتجربة أقل اتساقًا لمكونات العلاقة الإشرافية. وتناقش الدراسة تطبيقات الاستفسار المستقبلي حول أهداف RS و IECMH كاستراتيجيات لتعزيز تطوير القوى العاملة ورفاهيتها.